Neurochemical markers in CSF of adolescent and adult SMA patients undergoing nusinersen treatment. (May 2019) - Wurster, Claudia D.; Günther, René; Steinacker, Petra; Dreyhaupt, Jens; Wollinsky, Kurt; Uzelac, Zeljko; Witzel, Simon; Kocak, Tugrul; Winter, Benedikt; Koch, Jan C.; Lingor, Paul; Petri, Susanne; et al.
Background: There is limited information on neurochemical markers being used to support and monitor the affection of motoneurons in patients with spinal muscular atrophy (SMA). The objective of this study was to examine neurochemical markers in cerebrospinal fluid (CSF) under treatment with the antisense-oligonucleotide (ASO), nusinersen. Methods: We measured markers of axonal degeneration [neurofilament light chain (NfL) and phosphorylated neurofilament heavy chain (pNfH)] along with basic CSF parameters in 25 adolescent and adult SMA type 2 and 3 patients at baseline and after four intrathecal injections of nusinersen. Neurochemical markers were compared with controls. In addition, neurochemical markers in SMA patients were related to the Hammersmith Functional Rating Scale Expanded (HFMSE). Results: No significant difference in neurofilament (Nf) values was observed between SMA and control group, neither at baseline nor after four injections of nusinersen. NfL, protein and quotients of albumin (Qalb ) increased slightly in SMA patients after the fourth injection. The slight increase of NfL could be related to the development of mild CSF flow change. No relations were observed between changes in Nf and HFMSE. Conclusion: We assume that Nf levels in CSF in these patients may result from slow disease progression in this stage of disease, pre-existing loss of motoneurons due to long disease duration besides affection of the LMN only. Therefore, we conclude that Nf levels in CSF do not seem useful as diagnostic and monitoring markers in adolescent and adult SMA type 2 and 3 patients.